1990
DOI: 10.1111/j.1365-2494.1990.tb01951.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of three bacterial inoculants and formic acid as additives for first harvest grass

Abstract: An experiment was carried out during 1984 to study the effect of treating grass at ensiling with three commercially available inoculant-type additives {H/M Inoculant, Grass Sile and Siron), formic acid (850 g kg"'; Add-F) or no additive on grass preservation, in-silo loss, intake and animal performance. Primary growth grass ensiled from 28-29 May into concrete-walled covered silos was of high dry matter (DM, 234 g kg"'), water-soluble carbohydrate content (WSC. 212 g kg DM"') and digestibility (MADF, 250 g kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
0
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
9
11
0
4
Order By: Relevance
“…ment with the results of Appleton and Done (1987), Henderson et al (1988), Kennedy et al (1989),Kennedy (1990) and O'Kiely (1990Kiely ( ,1991, whereas Weddell (1986),…”
supporting
confidence: 63%
“…ment with the results of Appleton and Done (1987), Henderson et al (1988), Kennedy et al (1989),Kennedy (1990) and O'Kiely (1990Kiely ( ,1991, whereas Weddell (1986),…”
supporting
confidence: 63%
“…According to Kennedy (1990), the effect of an inoculant on animal performance may not be significant if the untreated silage is well preserved. When fed to rams (Table 3), the inoculated silage increased (P <0.05) the intake of DM, OM, CP and GE compared to the control, which agrees with Rooke et al (1988) and Rooke & Kafilzadeh (1994) when inoculated silage was fed to sheep as the sole feed.…”
Section: Resultsmentioning
confidence: 99%
“…In lucerne silage, however, the inoculant enhanced heterolactic fermentation, which is shown by a 61% lower lactic : acetic acid ratio in IC2X-treated than in C2X-treated lucerne silage. Bacterial inoculants have shown little e †ect on fermentation of grass silage in other experiments (Kennedy 1990 ;Sharp et al 1994). Bolsen et al (1992) found increased lactic acid concentration and decreased pH and acetic acid concentration when inoculant was applied with dextrose to Biomate' lucerne, but inoculant alone had only a small e †ect on fermentation products during the Ðrst days of ensiling.…”
Section: Silage Fermentation Productsmentioning
confidence: 97%